2020
DOI: 10.3390/ijms21041485
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Statins on the Aerobic Metabolism of Endothelial Cells

Abstract: Endothelial mitochondrial dysfunction is considered to be the main cause of cardiovascular disease. The aim of this research was to elucidate the effects of cholesterol-lowering statins on the aerobic metabolism of endothelial cells at the cellular and mitochondrial levels. In human umbilical vein endothelial cells (EA.hy926), six days of exposure to 100 nM atorvastatin (ATOR) induced a general decrease in mitochondrial respiration. No changes in mitochondrial biogenesis, cell viability, or ATP levels were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 46 publications
0
28
1
Order By: Relevance
“…The same group further reported in the same in vitro experimental model that even lower concentrations of atorvastatin (100 nM) elicited a decrease in both maximal respiration (as result of supercomplexes rearrangement) and the total cellular coenzyme Q10 content [ 24 ]. Interestingly, these authors also reported a significant increase in the expression of UCP2 protein in mitochondria isolated from the endothelial cells exposed to 100 nM atorvastatin [ 25 ]. Vevera et al [ 11 ] showed in an in vivo study that 4-week treatment with simvastatin reduced platelet respiration in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The same group further reported in the same in vitro experimental model that even lower concentrations of atorvastatin (100 nM) elicited a decrease in both maximal respiration (as result of supercomplexes rearrangement) and the total cellular coenzyme Q10 content [ 24 ]. Interestingly, these authors also reported a significant increase in the expression of UCP2 protein in mitochondria isolated from the endothelial cells exposed to 100 nM atorvastatin [ 25 ]. Vevera et al [ 11 ] showed in an in vivo study that 4-week treatment with simvastatin reduced platelet respiration in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Statins have been reported to cause uncoupling in rat myoblasts as shown by the pioneering work by Kaufmann et al [ 17 ]. More recently, Broniarek et al reported that atorvastatin (and, in some cases, pravastatin) causes uncoupling (increased LEAK respiration) in endothelial cells [ 52 ]. LEAK respiration is a dissipative component of mitochondrial respiration that is nonphosphorylating and determines heat production [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not find a significantly increased LEAK respiration between the statin–treated groups and the untreated controls in the experiments carried out in intact platelets. We speculate that the statin level in these patients was much lower as compared with the doses used in the majority of the ex vivo studies (up to 1000–fold higher than the plasma concentration of statins under therapeutic conditions) [ 17 , 34 , 35 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supercomplex formation is believed to be a very dynamic process and of great importance for regulation of mitochondrial respiration 42,43 . Recently, it has been demonstrated that endothelial cells changed their supercomplex formation in response to atorvastatin 44 . Supercomplex formation can be mediated by increased levels of ROS 45 .…”
Section: Discussionmentioning
confidence: 99%